PENERAPAN TAX REVIEW ATAS PAJAK PENGHASILAN BADAN SEBAGAI DASAR EVALUASI KEWAJIBAN PERPAJAKAN SALAH SATU YAYASAN PENDIDIKAN DI DENPASAR TAHUN 2018 - Ni Kadek Yuni Andayani; I Wayan Sudiana; I Putu Nuratama (UNHI Press, 2020)
Tax review is a review of the activities of the entire tax obligations in an corporate and the implementation of fulfilling these tax obligations starting from the method of calculation, deduction, deposit, payment and reporting to assess tax compliance that has been done. The purpose of this study is to review the fulfillment of tax obligations in 2018, one of the foundations in Denpasar has been fulfilled and in accordance with applicable tax regulations. This research was conducted at a foundation engaged in the field of education in Denpasar. Data collection is done by means of observation at the Foundation. This research was conducted quantitatively with descriptive analysis method, namely through the collection of Annual tax report and Financial Statements in 2018. The results showed that the Foundation had not fully deducted the Article 21 Income Tax object and there were differences in change in net fiscal assets between the Foundation s calculations and taxation.